1992
DOI: 10.1182/blood.v80.12.3235.bloodjournal80123235
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid and lymphoid chimerism after T-cell-depleted bone marrow transplantation: evaluation of conditioning regimens using the polymerase chain reaction to amplify human minisatellite regions of genomic DNA

Abstract: Determining both myeloid and lymphoid chimerism after T-cell-depleted allogeneic bone marrow transplantation (BMT) could be helpful in the understanding of the biology of engraftment and could provide a rational method of assessing the ability of different conditioning regimens to promote engraftment. We prospectively investigated the role of different pretransplant conditioning regimens in 29 leukemic patients post-BMT by assessing myeloid and T-cell chimerism using a rapid and sensitive polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Graft-versus-host disease (GVHD) is one of the main obstacles in allogeneic BM transplantation, which is now a powerful strategy for the treatment of congenital immunodeficiencies, hematological neoplasias [19,20] and aplastic anemia [21] in humans. However, the elimination of T cells from the donor BM (to prevent GVHD) is often associated with relapse of the malignancy or rejection of the BM graft [22]. In the murine model, it has been reported that NS cells prevent GVHD [23].…”
Section: Introductionmentioning
confidence: 99%
“…Graft-versus-host disease (GVHD) is one of the main obstacles in allogeneic BM transplantation, which is now a powerful strategy for the treatment of congenital immunodeficiencies, hematological neoplasias [19,20] and aplastic anemia [21] in humans. However, the elimination of T cells from the donor BM (to prevent GVHD) is often associated with relapse of the malignancy or rejection of the BM graft [22]. In the murine model, it has been reported that NS cells prevent GVHD [23].…”
Section: Introductionmentioning
confidence: 99%
“…If we consider a single normalized Bcr-Abl dose of < 10 À3 as a negative value and compare these data with RCP, the correlation between RCP and Bcr-Abl dose was 77%. relapse (Ba Èr et al, 1989(Ba Èr et al, , 1992Roy et al, 1990;Lawler et al, 1991;Mackinnon et al, 1992Mackinnon et al, , 1994Roux et al, 1992Roux et al, , 1993Gardiner et al, 1997;Bader et al, 1998). We have shown previously that mixed chimaerism, as found with cytogenetic analysis of bone marrow and RCP at 6 months after BMT, was not associated with a higher incidence of relapse.…”
Section: Qualitative Determination Of Bcr-abl Breakpoint Moleculesmentioning
confidence: 72%
“…The occurrence of MC after allogeneic transplantation is influenced by several factors, such as the patient's characteristics (underlying disease, age) (1), transplant procedures [type of transplant and manipulation of the graft, conditioning regimen, graft‐vs.‐host disease (GVHD) prophylaxis] (2–8) and the sensitivity of the technique used for the analysis of chimerism status (9, 10). Donor T lymphocytes (11, 12) and the dose of donor CD34 + progenitor cells infused (13) are important factors in achieving the engraftment.…”
mentioning
confidence: 99%